ANALISIS SENTIMEN MAHASISWA HKI STDIIS SEMESTER 3 KELAS A, B, D TERHADAP PUTUSAN NOMOR: 1622/PDT.G/2023/PA.JB DALAM KASUS CERAI GUGAT, HARTA BERSAMA DAN HADANAH - Muhammad Wahid Abdulloh; Salman Zulfahmi; Abd.Muthalib (Al-Majaalis : Jurnal Dirasat Islamiyah, 2024)
Disputes between husband and wife sometimes lead to divorce. Some cases of divorce are caused by husbands, such as domestic violence, not providing support, cheating and so on. Sharia provides a way for wives to file for divorce. This lawsuit is of course based on justifiable reasons. This research examines the sentiments of students majoring in Family Law (HKI) at STDIIS semester 3 classes A, B, D regarding Decree Number: 1622/Pdt.G/2023/PA.JB regarding divorce cases, division of joint assets, and hadanah. A quantitative approach is used to better understand students' perspectives on certain legal decisions. Data was collected through a structured questionnaire given to a sample of HKI STDIIS students in semester 3 classes A, B, D. The Naive Bayes method using the Rstudio application and Orange software, it was concluded that the method and software used were effectively able to produce reliable analysis results. The accuracy of the Naive Bayes method in classifying user sentiment is reflected in the high level of accuracy, namely 72.3%. With the help of Orange software, the sentiment analysis process becomes more efficient and reliable, as evidenced by the achievement of Precision: 76.4% Recall: 72.3% F1 Score: 73.4%. This combination of methods and software proves its ability to carry out in-depth and reliable sentiment analysis of STDIIS IPR Students' reviews of Decision Number 1622/Pdt.G/2023/PA.JB regarding divorce cases, division of joint assets, and hadanah.